Identification of Bacillus thuringiensis Cry3Aa toxin domain II loop 1 as the binding site of Tenebrio molitor cadherin repeat CR12. (April 2015) - Zúñiga-Navarrete, Fernando; Gómez, Isabel; Peña, Guadalupe; Amaro, Itzel; Ortíz, Ernesto; Becerril, Baltazar; Ibarra, Jorge E.; Bravo, Alejandra; Soberón, Mario
Abstract: Bacillus thuringiensis Cry toxins exert their toxic effect by specific recognition of larval midgut proteins leading to oligomerization of the toxin, membrane insertion and pore formation. The exposed domain II loop regions of Cry toxins have been shown to be involved in receptor binding. Insect cadherins have shown to be functionally involved in toxin binding facilitating toxin oligomerization. Here, we isolated a VHH (VHHA5) antibody by phage display that binds Cry3Aa loop 1 and competed with the binding of Cry3Aa to Tenebrio molitor brush border membranes. VHHA5 also competed with the binding of Cry3Aa to a cadherin fragment (CR12) that was previously shown to be involved in binding and toxicity of Cry3Aa, indicating that Cry3Aa binds CR12 through domain II loop 1. Moreover, we show that a loop 1 mutant, previously characterized to have increased toxicity to T. molitor, displayed a correlative enhanced binding affinity to T. molitor CR12 and to VHHA5. These results show that Cry3Aa domain II loop 1 is a binding site of CR12 T. molitor cadherin. Graphical abstract: Highlights: A VHHA5 antibody that binds Cry3Aa loop 1 was selected by phage display. Cry3Aa domain II loop 1 is a binding site to interact with BBMV from Tenebrio molitor. Cry3Aa domain II loop 1 is a binding site to interact with CR12 cadherin region. A Cry3Aa loop 1 mutant displayed enhanced binding affinity to CR12.